Hierarchical Omniphobic Surfaces for Pathogen Repellency and Biosensing - Moetakef Imani, Sara (My University, 2022)
Development of repellent surfaces which can supress bacteria adhesion, blood contamination and thrombosis, and non-specific adhesion on diagnostic devices has been a topic of intense research as these characteristics are in high demand. This thesis focused on design and development of omniphobic surfaces based on hierarchical structures and their application for preventing pathogenic contamination and biosensing. First, a flexible hierarchical heat-shrinkable wrap featuring micro and nanostructures, was developed with straightforward scalable methods which can be applied to existing surfaces. These surfaces reduced biofilm formation of World Health Organization-designated priority pathogens as well as minimized risk of spreading contamination from intermediate surfaces. This is due to the broad liquid repellency and the presence of reduced anchor points for bacterial adhesion on the hierarchical surfaces. Next, the developed surfaces were applied to minimize blood contamination and clot formation as well as facile integration of hydrophilic patterns. This led to droplet compartmentalization and was utilized for detection of Interleukin 6 in a rapid dip-based assay. Furthermore, in a review article the need for anti-viral or virus repellent surfaces and future perspectives were discussed as the global COVID-19 pandemic surged and attracted interest toward innovative technologies for suppressing the spread of pathogens. To address the pressing issue of non-specific adhesion in diagnostics devices, an omniphobic liquid infused electrochemical biosensor was developed. This was achieved by electroplating gold nanostructures on fluorosilanized gold electrodes. These electrodes demonstrated rapid and specific detection of Escherichia coli within an hour in complex biological liquids (blood, urine, etc.) without dilutions or amplification steps from clinical patient samples which are major bottle necks when rapid detection systems are sought for at the point of care.
Keywords: omniphobic surfaces; hierarchical surfaces; bacteria repellent; anti coagulant; biosensing; liquid infused surfaces; electrochemical biosensor; non-specific binding